Respuesta :

Answer:

Step-by-step explanation:

Ver imagen AmandaR84

Answer:

y = -3x + 25

Step-by-step explanation:

You have to find p first.

You can do this by using the x equation and moving the p to the right by adding p to each side to get p + x = 7.

Now, move the x to the left by subtracting x on both sides to get a final answer of p = 7 - x

Then, you can substitute p into the y equation.

So, y = 3(7 - x) + 4.

Distribute to get y = 21 - 3x + 4

Combine like factors to get y = -3x + 25

Hope this helps! :)